Revealing students' thinking schemes in solving direct current electrical circuit problems - Jeffry Handhika; Cari Cari; Suparmi Suparmi (Universitas PGRI Kanjuruhan Malang, 2025)
Students’ thinking schemes must be revealed to discover the students’ fundamental problems in solving direct current (DC) electrical circuit problems. Concept maps and problem-solving can be used to reveal students’ thinking schemes. The method used in this study is descriptive qualitative. The research was conducted on second-semester students who took the Fundamental Physics II course at a private university in Madiun in 2023/2024, totaling 9 students. Data was collected using the documentation method in the form of assignments to make concept maps, tests, and interviews. The results of this study reveal students’ thinking schemes, which can be categorized into computational thinking (CT), non-CT, and combined thinking (CT and non-CT). Non-CT students’ thinking schemes use trial and error methods to solve problems and intuition to conclude.